Measuring and Explaining the Increase of Travel Distance: A Multilevel Analysis Using Repeated Cross Sectional Travel Surveys - Oliver Lipps; Uwe Kunert (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Spatial mobility in the industrialised countries is ever increasing. In West-Germany the total mileage travelled annually by all modes of transportation grew by 40 % over the last two decades (1982 to 2002) to 900 billion kilometres, with the reliance on the use of the car becoming more pronounced. Now 80 % of travel as measured in kilometres is by car drivers and passengers.
Keywords: 330